THU0113 Differing Isotypes of the Anti-Citrullinated Peptide/Protein Antibodies in Palindromic Rheumatism and Rheumatoid Arthritis. (9th June 2015) - Cabrera Villalba, S.R.; Gomara, M.J.; Ramirez, J.; Salvador, G.; Ruiz-Esquide, V.; Hernandez, M.V.; Inciarte-Mundo, J.; Cuervo, A.; Cañete, J.; Sanmarti, R.
Abstract : Background: Palindromic rheumatism (PR) is an intermittent arthritis, may evolve to rheumatoid arthritis (RA), particularly in patients with citrullinated peptide/protein antibodies (ACPA), but not all patients progress to RA. Differences in ACPA isotypes have been shown between patients with established and preclinical RA. It is unclear whether ACPA isotypes differ between patients with longstanding PR and RA. Objectives: To determine whether there are differences in the recognition of epitopes between patients with longstanding PR and established RA by analysis of different ACPA fine specificities and isotypes Methods: Case-control study. Cases: patients with pure PR, with no evolution to RA or other rheumatic disease at study entry. Controls: patients with established RA (ACR-87) matched by sex, disease duration and ACPA positivity (commercial CCP2 test [Eurodiagnostica]; NV<50U). ACPA specificity in sera was determined by ELISA tests using different synthetic citrullinated peptides as antigens: [Cit 630] α-Fibrin (617-631), [Cit 64, 69, 71] Vimentin (47-72) and S 4, S 22 cyclo [Cys 4, 22, Cit 9, 15] Enolase (5-21), namely p18, p55 and CEP-1, respectively. The cut off for each ELISA test was established by ROC curves, with a specificity of 98% compared to a healthy population (blood donors, n=64). The presence and number of different ACPA isotypes (IgA, IgG, IgM) in both groups was analyzed. Results: We included 108 patients: 54 PR and 54 RA. 62.9% were female and 66.7% in both groups were CCP2 positive. No significant differences between groups in mean age (51.2±11.3 y vs 54.7±11.8 years) and disease duration (11.6±10.7 y vs. 8.3±6.1 years) were found. PR patients had a lower frequency of ACPA isotypes than RA, which was significant in the case of IgA and IgM against p18 (PR-IgA 18.5% vs RA-IgA 51.8%; p<0.001, and PR-IgM 13% vs 38.9% RA-IgM; p<0.001) and in IgA and IgG isotypes against p55 (PR-IgA 16.7% vs RA-IgA 38.9%; p<0.01, PR-IgG 24.1% vs RA-IgG 59.3%; p<0.001) (see Table 1 ). The mean number of ACPA isotypes was lower in PR than in RA patients. Conclusions: Patients with PR had a lower frequency of isotypes of ACPA than RA patients, especially in the case of p18 (isotypes IgA and IgM) and p55 (isotypes IgA and IgG). PR patients with fewer ACPA isotypes may have a better prognosis and without progression to RA. Disclosure of Interest: None declared